IMPLEMENTATION OF DESIGN THINKING APPROACH METHODS IN CURVING SELL MAINTENANCE WEBSITES (CASE STUDY: KAI DAOP 5 PURWOKERTO) - Br. Sihaloho, Yuni Novita; Fauzi, Akhmad; Safitri, Sisilia Thya (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
PT KAI DAOP 5 Purwokerto is one of Indonesia's railroad operating units under the auspices of PT Kereta Api Indonesia (Persero). PT KAI DAOP 5 Purwokerto has several divisions, one of which is the rail and bridge unit. The rail line and bridge units at KAI DAOP 5 Purwokerto are still manually recording plan data and inspecting tracks. So, a system is needed to record plan data and review railroad tracks. This is done to make it easier for inspection officers to store data and reduce the risk of losing data from inspecting railroad tracks. Methods of data collection using literature study methods, interviews, and discussions with prospective website users and the team. This research aims to assist users in recording planning data and to inspect rail lines and bridges. Designing a website using the Design Thinking approach can make it easier to make User Interface designs that suit user needs. Applying the Design Thinking approach, a prototype design was found, which was used as a reference in implementing the Sell Maintenance website. The results of tests conducted on one of the employees on the user interface design were 8 accepted, 2 rejected, and 3 revisions. Applying the Design Thinking approach, a prototype design was found, which was used as a reference in implementing the Sell Maintenance website. The results of tests conducted on one of the employees on the user interface design were 8 accepted, 2 rejected, and 3 revisions. Applying the Design Thinking approach, a prototype design was found, which was used as a reference in implementing the Sell Maintenance website. The results of tests conducted on one of the employees on the user interface design were 8 accepted, 2 rejected, and 3 revisions.